Evidence-based dentistry: Future aspects - Kanika Mohindra; Ashutosh Nirola (Wolters Kluwer Medknow Publications, 2017)
Traditionally, clinical decisions in dentistry have been based on the experience of the dentist. If the given treatment works, it was utilized again, but if the results were disappointing, the procedure was deserted. Evaluating clinical treatment in this fashion is difficult because it is hard to know which factors are important for success and which contribute to failure. This came with the concept of evidence-based approach which facilitates conclusions for clinical practice based on sound research studies.